Surgical Management of Rectal Prolapse - Review Article: Life Sciences-Health - Abood, Hashem Bark Awadh; Alghamdi, Faisal Abdullah A; Alqahtani, Osama Hassan; Abdrabalamir, Mohammed Abdulkareem; Albahar, Hassan Zuhair; Bader, Ahmed Hamzah; Muidh, Faris Mohammed; Farran, Osama Hashim; Aboshoushah, Anmar Lutfi; Bamaoudah, Ahmad Faisal; Alharthy, Saud Faiz; Altowairqi, Ziyad Khalid A; et al. (International Journal of Life Science and Pharma Research, 2022)
Rectal prolapse procidentia is an intussusception of the whole rectal wall through the anal canal, resulting in a portion of the rectum staying periodically or occasionally permanently distal to the anus. Full-thickness prolapse and partial-thickness prolapse are the two kinds of rectal prolapse. Rectal prolapse procidentia is an intussusception of the whole rectal wall through the anal canal, resulting in a portion of the rectum staying periodically or occasionally permanently distal to the anus. It is more frequent in older females. Rectal prolapse was first recorded on papyrus circa 1500 BC. Hippocrates described rectal prolapse therapy as hanging patient’s upside down from a tree, putting sodium hydroxide to the mucosa, and fixing for three days. Today, is mostly treated surgically. Perineal surgical repairs are typically well tolerated; however, they are linked with a greater incidence of recurrence. Abdominal repairs, however, have the lowest recurrence rates. The goal of therapy is to remove the prolapse, cure any related incontinence or constipation issues, and avoid de novo bowel dysfunction. When compared to laparotomy, laparoscopic rectopexy offers fewer side effects, a shorter hospital stays, faster healing, and quicker return to work. This review aims to assess recent updates on different surgical approaches for management of rectal prolapse.